Analysing the quality of Australian universities' student anti-bullying policies. Issue 6 (18th September 2020) - Vaill, Zoe; Campbell, Marilyn; Whiteford, Chrystal
ABSTRACT: Bullying has been a topic widely researched in schools and the workplace, however, comparatively there is a paucity of research into bullying among university students. This is an oversight, as bullying may also have negative consequences for university students, ranging from anxiety to suicidal ideation. Anti-bullying policies are an important part of bullying prevention and intervention, however, due to Australian Federal legislation, policies for students are not mandatory at universities. To be an effective prevention and intervention strategy, anti-bullying policies and procedures should be informative, supportive, well publicised, and student user friendly. Through analysing the anti-bullying policies and procedures from 39 Australian universities, using a 37-item analysis tool adapted from Purdy and Smith as well as thematic analysis, this study aims to determine if Australian universities are providing students with the information and support they need to be able to report bullying to their university and study in a safe environment. Both strengths and weaknesses were found in 37 individual universities' student anti-bullying policies and procedures, as well as overall trends displayed by universities Australia-wide. The overall paucity of information and consistency, as well as the poor user-friendliness of many of the documents, highlights the need for changes to be made. Without the reform of student anti-bullying policies and procedures in Australian universities, students will be unsupported and ill-equipped to identify and report bullying. Universities will also run the risk of gaining a bad reputation and not promoting a bully-free culture for students in which to learn and socialise.